Penentuan Kadar Fenol Total Dan Uji Aktivitas Antioksidan Kombinasi Ekstrak Herba Pegagan (Centella asiatica L. Urban) Dan Buah Mahkota Dewa (Phaleria macrocarpa(Scheff.) Boerl.) - Purgiyanti Purgiyanti; Anny Victor Purba; Hendig Winarno (Parapemikir : Jurnal Ilmiah Farmasi, 2019)
Many diseases that were originally caused by free radicals, so that free radicals and antioxidants observed extensively in the world of health. Gotu kola herb and fruit Mahkota Dewa were supposed to have antioxidant activity that can reduce the activity of free radicals. The purpose of this study was to determinethe total phenol content and the antioxidant activity of the combination of herbal extracts of Gotu kola (Centella asiatica L. Urban) and Mahkota Dewa fruit (Phaleria macrocarpa (Scheff.) Boerl.) Gotu kola herb extracts and Mahkota Dewa fruit extracts obtained by maceration using ethanol 70% with the ratio between crude drug powder and solvent was 1: 5. The antioxidant activity was determined by DPPH (2,2-diphenyl-1 picrylhydrazyl). Total phenol content was determined using UV-Vis spectrophotometry reagent Folin- Ciocalteau the results expressed in gallic acid equivalents (mg GAE / 100 g extract). The result shows that the combination of the ethanol extract of Centellaasiatica herb and Mahkota Dewa fruit in the ratio of 1: 1 has a total phenol content of 3.67 mg GAE / 100 g of extract and active as an antioxidant with IC50 value of 67.07 mg / mL, and vitamin C as active comparison as an antioxidant with IC50 value of 8.81 mg / mL. This study shows that a combination of herbal extracts between Gotu Kola and MahkotaDewa have potentials as natural antioxidants.Keywords— Gotu Kola herb, Mahkota Dewa fruit, total phenols, Folin-Ciocalteau,DPPH